2017
DOI: 10.1055/s-0043-118535
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Interference of Hemoglobin Variant J-Bangkok on Glycated Hemoglobin (HbA1c) Measurement by Five Different Methods

Abstract: The interference of the hemoglobin variant (Hb J-Bangkok) was evaluated on 4 different glycated hemoglobin assays and compared with a reference immuno assay. An overall test of coincidence of 2 least-squares linear regression lines was performed to determine whether the presence of Hb J-Bangkok caused a statistically significant difference in HbA1c results compared with a reference immuno assay. Statistical analysis was performed on the difference of the estimated average glucose calculated from HbA1c values a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…The principle of enzymatic determination of HbA1c is that glycated glycine glutamine from the β chain N-terminus of HbAlc is cut off by a specific protease. The specific cleavage site of HbA1c is not affected by Hb J-Bangkok ( 17 ).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The principle of enzymatic determination of HbA1c is that glycated glycine glutamine from the β chain N-terminus of HbAlc is cut off by a specific protease. The specific cleavage site of HbA1c is not affected by Hb J-Bangkok ( 17 ).…”
Section: Discussionmentioning
confidence: 98%
“…The accuracy of HbA1c in patients with hemoglobinopathy is method dependent. It has been reported that immunoassay and enzyme methods are not affected by Hb J-Bangkok ( 17 ). Immunoassays use specific antibodies to bind to glycated sites on the N-terminus of the Hb β chain of HbA1c, which is far from the location of the amino acid substitution of Hb J-Bangkok.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most cases of Hb J are clinically silent and mostly discovered incidentally during routine investigations or in conjunction with other hemoglobinopathies such as thalassemia [ 8 ] and sickle cell anemia [ 9 ] while investigating these diseases. Interestingly, there are many reports of Hb J interfering with glycated hemoglobin measurements in diabetics [ [10] , [11] , [12] ]. There are case report of Hb J being detected following transfusion as well [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, others interfere with immunoassay [ 18 ]. Being simple and cost-effective, the mathematical calculation of HbA1c is becoming of value in areas with insufficient resources [ 19 ]. In areas with low resources, such as our setting in northern Sudan, the availability of HbA1c assessment is a big issue; hence the calculated HbA1c is a reasonable solution to assess glycemic control [ 19 ].…”
Section: Introductionmentioning
confidence: 99%